SYNTHESIS AND CHARACTERIZATION OF MESOPOROUS ALUMINOSILICATES Al-MCM-41 AND INVESTIGATION OF ITS THERMAL, HYDROTHERMAL AND ACIDITY STABILITY - Suyanta Suyanta; Narsito Narsito; Endang Tri Wahyuni; Triyono Triyono (Universitas Gadjah Mada, 2010)
The synthesis and characterization of mesoporous aluminosilicates Al-MCM-41 and the investigation of its thermal, hydrothermal and acidity stability have been done. Al-MCM-41 were synthesized by hydrothermal method to the mixture of sodium silicate as Si source, aluminium hydroxide as Al source, sodium hydroxide as a solvent, and cethyltrimethylammoniumbromide (CTAB) as structure directing agent. The reaction were carried out in alkaline condition (pH = 10.2) at 383 K for about 24 h, followed by calcination at 723 K for about 10 h. The synthesized crystals were characterized using FTIR spectroscopy, X-ray diffraction and N2 fisisorption methods. The result showed that Al-MCM-41 sample with hexagonal structure was formed, it has a good in thermal and acid stability, but the structure disintegrated in an alkaline solution (pH = 10) and in boiled water.